2019
DOI: 10.18502/kss.v3i22.5054
|View full text |Cite
|
Sign up to set email alerts
|

An Error-Proof Approach for Decision Making Using DEMATEL

Abstract: Decision Making Trial and Evaluation Laboratory method of Multi-Criteria Decision Making has been being used very widely in many management studies (like Operation Management) to identify causal relationships among factors and draw attention to valuable insight for decision making. The scope of this system has reached the manufacturing industry, social activities, farming, financial system, environmental science, energy, and other areas, and has solved numerous practical problems. However, the author has found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Islam et al (2019) and other researchers conducted an extensive literature review and concluded that among the several multicriteria decision-making methods, DEMATEL is preferred due to the following reasons:The lesser need for experimental data and outstanding flexibility to identify patterns (Islam et al , 2019). Assurance of DEMATEL to competently yield outcomes using minimum data quantity (Islam et al , 2019). Comparatively not rigid (Islam et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Islam et al (2019) and other researchers conducted an extensive literature review and concluded that among the several multicriteria decision-making methods, DEMATEL is preferred due to the following reasons:The lesser need for experimental data and outstanding flexibility to identify patterns (Islam et al , 2019). Assurance of DEMATEL to competently yield outcomes using minimum data quantity (Islam et al , 2019). Comparatively not rigid (Islam et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assurance of DEMATEL to competently yield outcomes using minimum data quantity (Islam et al , 2019). Comparatively not rigid (Islam et al , 2019). DEMATEL offers several directional associations weighed against the analytical hierarchy process with merely a unidirectional association.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations